2020
DOI: 10.3390/genes11070769
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Encoding CENP-A and Heterochromatin Protein 1 of Lipomyces starkeyi and Functional Analysis Using Schizosaccharomyces pombe

Abstract: Centromeres function as a platform for the assembly of multiple kinetochore proteins and are essential for chromosome segregation. An active centromere is characterized by the presence of a centromere-specific histone H3 variant, CENP-A. Faithful centromeric localization of CENP-A is supported by heterochromatin in almost all eukaryotes; however, heterochromatin proteins have been lost in most Saccharomycotina. Here, identification of CENP-A (CENP-AL.s.) and heterochromatin protein 1 (Lsw1) in a Saccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…In particular, I have reported that the L. starkeyi heterochromatin protein Lsw1 can associate with heterochromatin in Sz. pombe in an H3K9 methylation‐dependent manner, suggesting that the expression of MAT locus genes might be repressed by heterochromatin via methylation of H3K9 (Takayama, 2020 ). Thus, analysis of the mechanisms of mating type switching using the newly isolated crossable strains, Ls75 and Ls100, might reveal a novel MAT determination system that is not dependent upon an IR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, I have reported that the L. starkeyi heterochromatin protein Lsw1 can associate with heterochromatin in Sz. pombe in an H3K9 methylation‐dependent manner, suggesting that the expression of MAT locus genes might be repressed by heterochromatin via methylation of H3K9 (Takayama, 2020 ). Thus, analysis of the mechanisms of mating type switching using the newly isolated crossable strains, Ls75 and Ls100, might reveal a novel MAT determination system that is not dependent upon an IR sequence.…”
Section: Discussionmentioning
confidence: 99%